2012
DOI: 10.2332/allergolint.10-oa-0295
|View full text |Cite
|
Sign up to set email alerts
|

Cough Triggers and Their Pathophysiology in Patients with Prolonged or Chronic Cough

Abstract: Several cough triggers may reflect the pathophysiology of prolonged or chronic cough.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 31 publications
3
27
1
4
Order By: Relevance
“…Chronic cough can result from hypersensitivity to environmental factors, such as chemicals, scents, cold air, and smoke [125], but there are only two reports of an association between Asian dust and chronic cough symptoms. The preliminary study from Higashi et al [126] indicates that Asian dust triggers cough and allergic symptoms in adult patients suffering from chronic cough.…”
Section: Desert Dust and Other Respiratory Diseasesmentioning
confidence: 99%
“…Chronic cough can result from hypersensitivity to environmental factors, such as chemicals, scents, cold air, and smoke [125], but there are only two reports of an association between Asian dust and chronic cough symptoms. The preliminary study from Higashi et al [126] indicates that Asian dust triggers cough and allergic symptoms in adult patients suffering from chronic cough.…”
Section: Desert Dust and Other Respiratory Diseasesmentioning
confidence: 99%
“…Exposure to environmental irritants, including ambient pollutants known to trigger cough both in children and adults, has been reviewed [8,9,10]. In addition, there is evidence from cross-sectional studies that have shown the association in adults [11,12]. Although longitudinal studies have also been performed in Europe and North America [13,14] with some inconsistent results, few have specifically studied ambient polycyclic aromatic hydrocarbons (PAH) among adults [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…7 A Japanese group evaluated the association of patient reported triggers with cough, including GERD induced symptoms. 8 Of 194 patients, only 19 had GERD as defined by questionnaire scores (Frequency Scale for Symptoms of GERD and QUEST – questionnaire for the diagnosis of reflux disease). These patients were more likely to report “spices” and “meals” as triggering cough and higher questionnaire scores were independently associated with cough symptoms.…”
Section: Approach To Diagnosis In Gastroenterologymentioning
confidence: 99%